Improving the Directional Decision Algorithm of Protective Devices for the Increasing Interconnection of Distributed Generation - Yun, Sangwon; Jung, Jaesung; Cho, Namhun (IEEE Power and Energy Society General Meeting, 2019)
Directional protective devices are utilized for reliable protection coordination in distribution system with Distributed Generation (DG). However, directional decision algorithm of Korea Electric Power Corporation (KEPCO) has found a problem to detect the correct direction when zero-sequence voltage is lower than the threshold value. This paper proposes new directional decision algorithm to solve this problem. For this, the existing algorithm and its problem are investigated. Then, the characteristic of fault current is analyzed according to the fault location in distribution system with DG. Based on the analysis, the improved algorithm is proposed. Finally, it is verified that the proposed algorithm can determine the correct direction regardless of lower zero-sequence voltage than threshold value.
Keywords: Decision algorithms; Distribution systems; Electric power corporation; Protection coordination; Protective devices; Threshold-value; Zero sequence voltage; Directional Decision Algorithm; Directional Protective Device; Distributed Generation; Distribution System